Role of Pro- and Antioxidant Properties of Biologically Active Substances When Increasing Cell Resistance to Hypothermia and Cryopreservation - Kabachny, V. I.; Gorbunova, N. I. (Problems of Cryobiology and Cryomedicine, 2004)
The effect of biologically active substances (BAS) with different chemical origin nature on lipid peroxidation (LPO) processes in the membranes and an antioxidant (AO) enzyme system in bovine spermatozoa under hypothermia and cryopreservation, was under study. The regulation of balance between pro- and antioxidant cell systems with participation of K321 and K322 heteroside derivatives provides a cell resistance to cooling, that is manifested by an increase in the motility of frozen-thawed cells by 33.6 (p<0.05) and 44.6% (p<0.05), correspondingly in comparison with the control. The motility stimulation in native spermatozoa with pentoxifylline (PF) and caffeine (CF) is accompanied with LPO increase, that can be one of the factors of a decrease in their functional activity after cryopreservation.